West Africa faces mixed food security impacts from the Russia-Ukraine conflict - Bouët, Antoine; Laborde Debucquet, David; Traoré, Fousseini (International Food Policy Research Institute, 2023)
Food security in West Africa has been deteriorating since 2015: The proportion of the population affected by undernutrition rose from 11.5% in 2015 to 18.7% in 2020, a total of 75.2 million people. Now, like the rest of the world, the region faces rapidly growing impacts from Russia’s war in Ukraine, including spiking food prices and disruptions in markets for cereals and other commodities, including fertilizers and fuels. What are some of the war’s likely effects on West Africa? Overall, the greatest risk is from rising global prices. The region imports relatively little food or fertilizer (with some exceptions) from Russia and Ukraine, insulating it from many of the current market disruptions, and has capacity to substitute some lost fertilizer imports.